Patient-reported outcomes of retropubic versus trans-obturator mid-urethral slings for urinary stress incontinence: the Malaysian experience - Nusee, Zalina; N., Kamal; Naidu, Aruku; Ab Rahman, Jamalludin (Faculty of Medicine, International Islamic University Malaysia, 2013)
Introduction: Studies reported that trans-obturator mid-urethral sling (TOT) is superior in safety and efficacy when compared with retro-pubic trans-vaginal tape (TVT) with regard to bladder, vascular and urethral injury. The purpose of this study is to determine if the TOT is equivalent to the TVT by using patient-reported outcomes for the treatment of urodynamic stress urinary incontinence (USI) at Ipoh Hospital. Methods: It is a cross-sectional study on all consecutive patients who underwent TVT procedure between Jan 2005 and Jan 2006 and TOT procedure from Jan 2006 to Jun 2008. Post operatively; all women were followed up at one month, three months, 12 months and annually, thereafter. Data was retrieved from the patients’ records based on the standard pre-operative assessment sheet and follow up record. Then, interviews were made via a telecommunication to assess the patients’ symptoms and satisfaction using a validated questionnaire. Data analysis were performed using IBM SPSS Statistics for Windows version 19 (SPSS Inc., Chicago, Illinois) considering a significant level of P < 0.05. Results: Total of 51 subjects in TVT group and 52 in TOT group were available for analysis. At 12 months, the stress urinary incontinence (SUI) cure rate is higher in the TVT (90.2%) compared to TOT (80.8%) group; however, it was not statistically significant (p=0.279). The lower urinary tract symptoms (LUT) were improved post-operatively in both groups with urgency and urgency incontinence being significantly better in the TVT group. Four (7.4%) subjects in the TVT group had a bladder perforation (p=0.992) and one case of vaginal erosion reported in the TOT group. Conclusion: TVT had a higher successful rate in the treatment of SUI; however, it increases the risk of bladder perforation. Over active bladder symptom (OAB) were significantly improved in the TVT compared to TOT group